Pemasaran Hijau Yang Semakin Menjadi Kebutuhan Dalam Dunia Bisnis - Situmorang, James Rianto (Business Administration Study Program - Universitas Katolik Parahyangan, 2011)
Green marketing is a type of marketing where a company sells a product that is envi-ronmentally friendly. In the concept of green marketing, a company has done greenmarketing since the beginning of the production process which transform raw materi-als into environmentally friendly finished product, called green product. The growingglobal warming make the green marketing is a major issue in todayâs business world.Green marketing has become a necessity for both producers and consumers for thecreation of a healthy environment. A company can do green marketing that matchesto the companyâs business. Implementation of green marketing can cover many ac-tivities depending on what the company wants to do. Automotive manufacturers arean example of a company that must implement a comprehensive green marketingbecause its products could potentially damage the environment due to pollution fromvehicle fumes.Keywords: Green marketing, environment, green product, business